EFFECT OF DIFFERENT BRANDS OF ACTIVATED CARBON ON GROWTH AND DEVELOPMENT OF COCONUT (Cocos Nucifera L) EMBRYOS IN VITRO - Zosimo S. Bonaobra III; Erlinda P. Rillo; Osmundo D. Orense (International Coconut Community, 1998)
The effect of different brands of activated charcoal [Merck GR (Art. 2186), Sigma acid washed (C‑4386), Sigma neutralized (C‑3790), and Duchefa neutralized (C‑1302)] on growth and development ofcoconut zygotic embryos in vitro was evaluated. Analysis of data noted after one month revealed that there was no significant difference on percentage germination, shoot length, and number ofprimary root of cv. Laguna Tall embryos cultured in Y3 liquid medium supplemented with 2.5gll AC of different brands. Length of primary root of embryos cultured in Duchefa neutralized AC was significantly different from those in Sigma neutralized AC only after one month from initial culture. For the succeeding periods (2‑4 months), no significant difiference was observed among the treatments in terms of increment in plant height, number of scale and true leaves and length ofprimary root. Statistical analysis revealed thatpercentage ofseedlings with primary, secondary and tertiary roots did not differ significantly among the treatments 1‑4 months from initial culture. Results suggest that any brand (even alternately) can be used satisfactorily in the in vitro culture of coconut embryos.